2018
DOI: 10.1111/jace.16098
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐phase glass‐ceramics containing CaF2: Er3+ and ZnAl2O4:Cr3+ nanocrystals for optical temperature sensing

Abstract: Oxyfluoride transparent glass-ceramics (GC) containing CaF 2 and ZnAl 2 O 4 nanocrystals have been fabricated with melt-quenching method. By carrying out the heat treatment of the precursor glass (PG), Er 3+ and Cr 3+ were selectively partitioned into CaF 2 and ZnAl 2 O 4 nanocrystals, respectively. The obtained multiphase GC exhibited strong upconversion (UC) fluorescence of Er 3+ as well as intense down-conversion (DC) fluorescence of Cr 3+ . Under 980 nm excitation, the green UC fluorescence of Er 3+ due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…26 For instance, the excited-state lifetimes in some Cr 3+ -doped inorganic phosphors have been reported to be in the millisecond time range. [27][28][29] To the best of our knowledge, surface-enhanced luminescence (SEL) of inorganic phosphors has not been studied. In this work, we report on the SEL of two chromium-doped spinels (CDSs) with lifetimes in the millisecond range at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…26 For instance, the excited-state lifetimes in some Cr 3+ -doped inorganic phosphors have been reported to be in the millisecond time range. [27][28][29] To the best of our knowledge, surface-enhanced luminescence (SEL) of inorganic phosphors has not been studied. In this work, we report on the SEL of two chromium-doped spinels (CDSs) with lifetimes in the millisecond range at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Matsui et al (2001) observed mechanooptical stress sensing in ZnAl 2 O 4 doped with Mn 2+ . Optical temperature sensing through temperature-dependent fluorescence up-and down-conversion in ZnAl 2 O 4 :Cr 3+ ,Er 3+ , attributed to the selective partitioning of optical centres, was explored by Wadhwa et al (2019). Most recently, saturation absorption of Fe 2+ ions in Fe:ZnAl 2 O 4 was studied using Ho:YAG and Er:YAG lasers by Fedorov et al (2020) for mid-IR laser applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Ba 2 LaF 7 :Ln 3+ containing glass-ceramics have extraordinary UC luminescence property, being a potentially candidate for random lasing action, [4,5] optical thermometry, [6] and green phosphors in white light-emitting diodes. [9][10][11][12] Previous researches revealed that the unique connection between the chemical state of dopants and topology of the disordered glass structure in oxide glass system. [8] Different luminescent centers have coordination preferences in oxide or fluoride environment.…”
Section: Introductionmentioning
confidence: 99%
“…Different luminescent centers have coordination preferences in oxide or fluoride environment. Normally, most of the Ln 3+ is found to enrich in the fluoride phase, while the transition metal ions can enrich in the oxide or fluoride phase depending on other glass modifier cations in the composition . Previous researches revealed that the unique connection between the chemical state of dopants and topology of the disordered glass structure in oxide glass system .…”
Section: Introductionmentioning
confidence: 99%